Analisis Zat Kimia Berbahaya Dan Kepunahan Biota Dalam Fisika Lingkungan - Parinduri, Fitriani; Parinduri, Sri Handayani; Nasution, Ahmad Juned (Gravity Journal, 2024)
The purpose of this research is to analyse hazardous chemicals and biota extinction in environmental physics. This type of research is descriptive qualitative using survey research procedures through literature study and field study.          Literature study was conducted through literature search from books and reputable online sites. Field studies were conducted through observations related to environmental pollution around the residences of VII semester students who took environmental physics courses. The results showed that there are various types of hazardous chemicals that cause biota extinction in environmental physics.